2019
DOI: 10.1108/gm-06-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the effect of government support on the relationship between gender egalitarian and women leadership effectiveness among public universities in KSA

Abstract: Purpose Even though nowadays more women occupy leadership roles, they still are a minority. Because aspiration is a precursor of advancement, examining conditions fostering female leadership aspiration is important, particularly in the context of Saudi Arabia where moral relativism play a vital role. This paper aims to discuss these issues. Design/methodology/approach A cross-sectional survey design with 500 full-time employed women, working in Saudi Arabia Public University were selected using quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…The results are consistent with Gorondutse et al (2019) that equality between man and woman and governmental support for woman reinforce the effectiveness of her role in leadership positions. The result is consistent with Al-Zahrani and Al-Hamami (2018) that the obstacles related to the community's perception of the woman greatly impede her empowering.…”
Section: Resultssupporting
confidence: 84%
“…The results are consistent with Gorondutse et al (2019) that equality between man and woman and governmental support for woman reinforce the effectiveness of her role in leadership positions. The result is consistent with Al-Zahrani and Al-Hamami (2018) that the obstacles related to the community's perception of the woman greatly impede her empowering.…”
Section: Resultssupporting
confidence: 84%
“…The last factor is GS which explains 6.297% of variation and consists of only three items. Although it may not appear to have a significant influence, researchers have considered the effects of GS as a key area of concern for empowering women and past studies have identified the critical role of governments in fostering the use of digital banking, which serves as a catalyst for WEE (Jaruwachirathanakul, 2003; Gorondutse et al , 2019). Furthermore, since the Indian economy was liberalized, the evolving government policy environment has provided prospects for long-term self-employment in India (Dana, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Women's under-representation in leadership positions (Al-Rasheed, 2013) is changing as they are increasingly occupying influential leadership positions in organizations (Thompson, 2015). To support and strengthen this trend and momentum, there is a need to enhance the aspirations and effectiveness of women leaders in HEIs, and this requires a deeper understanding of their experiences within HEIs (Gorondutse et al, 2019), as well as a deeper knowledge of Educational Leadership and Management (EDLM) in Saudi Arabia. As identified by Hammad et al (2022, p. 17) in their review of EDLM scholarship in the Arab Gulf, "Saudi Arabia has the largest higher education system in the region.…”
Section: Women's Leadership Within the Saudi Hei Contextmentioning
confidence: 99%